2005
DOI: 10.1007/s00264-005-0668-0
|View full text |Cite
|
Sign up to set email alerts
|

Plate augmentation leaving the nail in situ and bone grafting for non-union of femoral shaft fractures

Abstract: We reviewed 15 patients with femoral nonunion after interlocking intramedullary nailing treated with plate augmentation and bone grafting with the nail in situ. The mean time from primary nailing to plate augmentation and bone grafting was 10 months. At the time of presentation, the patients had undergone an average of 1.6 operations from the time of their original injury. To achieve stability of the fracture, we applied an AO plate on the lateral aspect of the femur. The retained nail maintained alignment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
2
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 17 publications
(20 reference statements)
1
52
2
6
Order By: Relevance
“…Reamed exchange nailing was widely accepted as the treatment of choice for the nonunion of femoral shaft fracture, but a significant number of patients who had undergone reamed exchange nailing required additional procedures to achieve union of the fractures [3,16]. Choi et al [2] reported successful bony union with plate augmentation leaving the nail in situ for unstable femoral nonunion. Ueng et al [15] and Nadkarni et al [11] achieved successful bony union with plate augmentation in the presence of intramedullary nailing for femoral nonunion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reamed exchange nailing was widely accepted as the treatment of choice for the nonunion of femoral shaft fracture, but a significant number of patients who had undergone reamed exchange nailing required additional procedures to achieve union of the fractures [3,16]. Choi et al [2] reported successful bony union with plate augmentation leaving the nail in situ for unstable femoral nonunion. Ueng et al [15] and Nadkarni et al [11] achieved successful bony union with plate augmentation in the presence of intramedullary nailing for femoral nonunion.…”
Section: Discussionmentioning
confidence: 99%
“…The retained nail acts as a useful loadsharing device, neutralising shear forces at the fracture site and maintaining alignment of the fracture [12]. Choi et al [2] reported successful bony union with plate augmentation leaving the nail in situ for unstable femoral nonunion. Many surgeons ask about the mechanical role of plate augmentation after interlocking intramedullary nailing whenever authors present the clinical results at meetings.…”
Section: Introductionmentioning
confidence: 99%
“…efectuaron aumento con placas y colocación de injerto óseo en todos sus pacientes con no uniones mediodiafisarias de fémur, sin discriminar entre atróficas e hipertróficas, y lograron la consolidación en un tiempo de 7,2 meses en promedio. 15 En nuestra serie, utilizamos el injerto de hueso en las seudoartrosis atróficas, ya que, en estos casos, se requiere un aporte biológico extra al aumento de la estabilidad con la placa. En ninguno de los 4 casos de seudoartrosis hipertrófica, se colocó injerto óseo, porque la consolidación se lograría solamente aumentando la estabilidad del foco con la colocación de la placa.…”
Section: Discussionunclassified
“…In addition, reliable results have been reported for augmentation plating after intramedullary nailing for nonunions in the lower extremities. The technique takes advantage of the high axial stiffness resulting from in situ nails and uses short plates to minimize adverse rotational micromovements without compressing the nonunion site [9]. Placement of a second plate on a 90° plane or, alternatively, a strong on lay cortical bone graft or an intramedullary fibular allografts has been reported to enhance stability at the nonunion site.…”
Section: Discussionmentioning
confidence: 99%